1967
DOI: 10.1002/1097-0142(1967)20:5<623::aid-cncr2820200508>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of uterine cervix in Indian women.Results of the population screening program

Abstract: There is no invasive cancer which at one stage was not cancer‐in‐situ. The cervical cancer if detected at its pre‐invasive stage is amenable to treatment with 100% survival rate. The knowledge that cancer is preventable if detected in its precancerous stage or is curable if detected in its early stage strongly supports the need for routine cytological examination of all young females from time to time for detection of cervical neoplastic lesion in its early stage and a follow‐up of all the dysplastic lesions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Preponderance of CIN among parous was also noted by other workers. 12 Present study showed an increasing trend in the occurrence of CIN with age and parity.…”
Section: Discussionmentioning
confidence: 52%
“…Preponderance of CIN among parous was also noted by other workers. 12 Present study showed an increasing trend in the occurrence of CIN with age and parity.…”
Section: Discussionmentioning
confidence: 52%